Neoadjuvant Systemic Therapy Prior to Radical Prostatectomy for Clinically Localized High-Risk Prostate Cancer - Perera, Marlon; Beech, Benjamin B.; De Jesus Escano, Manuel; Gmelich, Caroline; Yip, Wesley; Boorjian, Stephen A.; Eastham, James A. (Frontiers in Urology, 2022)
Radical prostatectomy (RP) remains a standard treatment option for clinically localized high-risk prostate cancer. While RP provides excellent local control, patients with high-risk disease remain at considerable risk for recurrence after surgery. Disease relapse may be the result of occult distant metastases or regional micrometastatic disease at the time of surgery. Accordingly, the role of systemic (neoadjuvant) therapy prior to RP has been investigated. Proposed neoadjuvant regimens: include monotherapy or combinations of chemotherapy, hormonal deprivation, and immunologic agents. Randomized trials using androgen deprivation have demonstrated improved pathologic outcomes, including pathologic downstaging and decreased risk of positive surgical margins, extracapsular extension, and seminal vesical invasion. However, these, albeit early, trials did not reliably demonstrate improved post-prostatectomy oncologic outcomes. More recent trials have evaluated novel combinations of chemo-hormonal therapy and immunologic based therapies. These studies are currently maturing and offer the promise, pending findings, of potentially informing future practice. In this review, we highlight the pathophysiologic basis and contemporary evidence for neoadjuvant therapy prior to RP for clinically localized high-risk prostate cancer.